2005
DOI: 10.1309/73h7k7ubw816pbjj
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Automated Immature Granulocyte Count as a Predictor of Neonatal Sepsis

Abstract: Neonatologists use immature granulocytes (IG) in manual differential counts as an indicator of sepsis. This study was designed to compare the predictive ability of automated vs manual IG counts for neonatal sepsis. Infants undergoing sepsis evaluation were identified prospectively for study if a CBC count was obtained in temporal proximity to the blood culture. Automated IG counts were obtained from the research software of the Sysmex XE-2100 (Sysmex, Kobe, Japan). Manual average IG counts were obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
3
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 0 publications
1
51
3
5
Order By: Relevance
“…Also in preterm hospitalized infants elevations of IGs were associated with positive blood culture results. In this study, values exceeding 0.5% showed a more than three-fold increased likelihood of a positive blood culture (Nigro et al, 2005).…”
Section: Automated Detection Of Immature Granulocytes-clinical Applicmentioning
confidence: 42%
“…Also in preterm hospitalized infants elevations of IGs were associated with positive blood culture results. In this study, values exceeding 0.5% showed a more than three-fold increased likelihood of a positive blood culture (Nigro et al, 2005).…”
Section: Automated Detection Of Immature Granulocytes-clinical Applicmentioning
confidence: 42%
“…Interestingly, the imprecision of IG on the XN-9000 seems even better than that of IG compared with the previous generation Sysmex analyzers and OM. (6,7,10) The analysis of bias shows that the XN-9000 exhibits a trend towards overestimation of both IG# and IG% compared to OM, an aspect that was previously described by Maenhout et al (9) However, unlike data reported by Maenhout, in our study the diagnostic accuracy of IG# and IG% on XN-9000 was characterized by significantly better AUC (p <0.0001) than those exhibited by the same parameters obtained with OM (OM-IG # and OM-IG% ) (table 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Recent studies have examined its ability to predict infectious conditions. 22,23,28,29 In this study, we investigated the usefulness of DNI as an early predictor of appendiceal perforation in elderly patients. (Figure 1).…”
mentioning
confidence: 99%